GP.03 Outcomes after gastrostomy tube placement in patients with acute stroke: A 10-year population-based study using the Ontario Stroke Registry. (June 2017) - Joundi, R; Saposnik, G; Martino, R; Fang, J; Giannakeas, V; Porter, J; Kapral, M
Abstract : Background: Dysphagia is a common and devastating complication after acute stroke. Percutaneous endoscopic gastrostomy (PEG) tubes are often placed for persistent dysphagia. However, little is known regarding outcomes after PEG tube placement.Methods: We used a 10-year Ontario Stroke Registry to shed light on the clinical outcomes of patients with PEG tube insertion after ischemic stroke or intracranial hemorrhage compared to patients with only NG tubes, including rate of pneumonia, disability, and mortality.Results: Using propensity score matching, 1, 793 patients were successfully matched and had similar baseline characteristics. Compared with NG, patients with PEG had a higher rate of pneumonia (32.6% vs. 20.6%; RR 1.59), higher disability at discharge (modified Rankin Scale Score 3-5; 74.0% vs. 65.4%; RR 1.13), and higher rate of long-term care placement (27.1% vs. 9.3%; RR 2.9). >From stroke onset, there was a lower rate of death in patients with PEG compared to NG at 30 days (15.3% vs. 34.3%; RR 0.45) but no difference at 2 years (52.8% vs. 53.5%; RR 0.99, p=0.71). *All significant p <0.0001.Conclusions: In conclusion, PEG tube placement after stroke may prolong survival in patients with poor outcomes. Our study provides a framework for discussions between physicians, patients, and families with regards to expected prognosis after PEG tube placement.